Laparoscopic Repair of Inguinal Hernia with Biomimetic Matrix - Fine, Arthur (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND AND OBJECTIVES: Materials utilized for the repair of hernias fall into 2 broad categories, synthetics and biologics. Each has its merits and drawbacks. The synthetics have a permanent, inherent strength but are associated with some incidence of chronic pain. The biologics rely on variable tissue regeneration to give strength to the repair, limiting their use to specific situations. However, thanks to their transient presence and tissue ingrowth, the biologics do not result in a significant incidence of chronic pain. We studied the use of a biomimetic (REVIVE, Biomerix Corporation, Fremont, CA) in this setting in an attempt to obviate the disadvantages of each material. METHODS: Fourteen patients underwent laparoscopic repair by totally extraperitoneal and transabdominal preperitoneal techniques of 16 inguinal hernias. Follow-up was as long as 19 mo, and 8 patients were followed for > 12 mo. There were no recurrences and a 5% incidence of functionally insignificant discomfort. RESULTS: REVIVE is shown in histology and in vivo to demonstrate regeneration and tissue ingrowth into the polycarbonate/polyuria matrix similar to that in the biologics rather than scarring or encapsulation. There were no recurrences, indicating its strength and resilience as a permanent repair similar to that in the synthetics. CONCLUSION: This is proof of the concept that a biomimetic may bridge the gap between the biologics and synthetics and may be able to be utilized on a regular basis with the benefits of both materials and without their drawbacks.